2014
DOI: 10.5424/fs/2014231-03297
|View full text |Cite
|
Sign up to set email alerts
|

Radial variations of wood different properties in Diospyros lotus

Abstract: Aim of study: The aim of this study was to determine some of the physical, biometry and mechanical strength properties of Diospyros lotus L. wood along radial direction from the pith to the bark and the relationship between wood various properties.Area of study: The study area is located in north Iran in the province of Mazandarn. Material and methods:Testing samples were taken at breast height of tree stem and three radial position of stem radius to determine physical (basic density), fiber biometry (fiber le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Furthermore, it has been used as herb tea and the treatment of hypertension in patients for long time in Korea [19][20][21]. However, many researches focused on the fruits and timer, little studies have been done for comprehensive use of the persimmon leaves [22][23][24]. The objective of the present study was to investigate the constituents of the leaves extracts of Diospyros lotus L. by FT-IR, GC-MS, and MTT analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been used as herb tea and the treatment of hypertension in patients for long time in Korea [19][20][21]. However, many researches focused on the fruits and timer, little studies have been done for comprehensive use of the persimmon leaves [22][23][24]. The objective of the present study was to investigate the constituents of the leaves extracts of Diospyros lotus L. by FT-IR, GC-MS, and MTT analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As free water is removed from the cell lumen till the point it reaches the bound water in the cell wall, which is the fibre saturation point and beyond, the cells tend to move closer and become compacted. The movement in the tangential and radial directions is several times greater than in the longitudinal direction [31] and that tends to make shrinkage more prominent than in the longitudinal direction.…”
Section: ) Volumetric Shrinkagementioning
confidence: 94%
“…The analysis of variance at a 95% confidence level revealed that there is a significant difference among the sampled trees, the axial direction as well as the radial positions in wood. The increase in density from the innerwood to the outerwood may have been a result of an increase in the age of the cambium (tree age) [12] [25] [31].…”
Section: Wood Densitymentioning
confidence: 99%
“…The timber of Diospyros lotus L. is rare dark wood and used as fine furniture and stationery for beautiful texture and color. The timber chemical properties are an important aspect for wood properties and utilization [18,19]. Some of these ingredients are important raw materials for many sectors such as chemical industry, medicine and light chemical industry, and have certain economic value [20].…”
Section: Introductionmentioning
confidence: 99%